Large-Eddy Simulation of Wind Flow within a Canyon between Modified Idealized Terraced Houses / Mohamad Nor Hafidz Arif Razali...[et al.] - Hafidz Arif Razali, Mohamad Nor; Shaikh Salim, Sheikh Ahmad Zaki; Mat Ali, Mohamed Sukri; Ahmad, Nurul Huda (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
Adequate wind flow in residential neighbourhood is important for providing a comfortable and healthy environment. It can significantly affect the diffusion of heat; lowering the temperature around it, and the dispersion of traffic-related pollutants between urban surfaces and the atmosphere. In this study, large-eddy simulation, using the Smagorinsky subgrid-scale model, was used to investigate the effect that modifications to a terraced house canyon would have on its wind flow characteristics. The configuration of an idealized terraced house canyon includes a height-to-width ratio h/w = 1/3, and secondary-roughness elements were installed in a staggered, square layout, at 0.5h from the ground. Secondary-roughness elements are treated as modifications to a terraced house building (large-roughness elements). The interaction between an idealized terraced house canyon and secondary-roughness elements has been studied by estimating wind velocity profiles within the terraced house canyon. The velocity profiles have been compared with previous studies to validate the accuracy of the simulation. This study reveals that the modification of the canyon can also affect the wind flow regimes, which might alter the micro climate in the surrounding area, owing to smaller canyon width and sheltering effect from the new obstacle.